Tradução e revelação: a recepção dos nomes divinos na tradução da Antígona de Sófocles por Hölderlin (Nuntius Antiquus, 2012)
Abstract: This paper aims to analyze the German poet Friedrich Hölderlin’s reception of the Greek tragedy, by examining his translations of two of Sophocles’ tragedies – Oedipus the King and Antigone –, which became a model for translation theory later on the 20th century. It intends to demonstrate Hölderlin’s peculiar view of Greece, acknowledged in the background of his work, which is reflected on the religious patterns of his translation, as he emphasizes the divine elements of Sophocles’ plays. This is more explicit in his transgressions of the original text, especially where he translates the Greek gods’ names.